2011
DOI: 10.1017/s0960129511000454
|View full text |Cite
|
Sign up to set email alerts
|

Bisimulations for non-deterministic labelled Markov processes

Abstract: We extend the theory of labelled Markov processes to include internal non-determinism, which is a fundamental concept for the further development of a process theory with abstraction on non-deterministic continuous probabilistic systems. We define non-deterministic labelled Markov processes (NLMP) and provide three definitions of bisimulations: a bisimulation following a traditional characterisation; a state-based bisimulation tailored to our ‘measurable’ non-determinism; and an event-based bisimulation. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 18 publications
0
48
0
Order By: Relevance
“…The semantics of IOSA is defined in terms of non-deterministic labeled Markov processes (NLMP) [14,26] which extends LMP [15] with internal non-determinism. The foundations of NLMP is strongly rooted in measure theory, hence we recall first some basic definitions.…”
Section: Semantics Of Iosamentioning
confidence: 99%
See 2 more Smart Citations
“…The semantics of IOSA is defined in terms of non-deterministic labeled Markov processes (NLMP) [14,26] which extends LMP [15] with internal non-determinism. The foundations of NLMP is strongly rooted in measure theory, hence we recall first some basic definitions.…”
Section: Semantics Of Iosamentioning
confidence: 99%
“…This is only guaranteed by the following proposition. Larsen and Skou's probabilistic bisimulation [21] has been extended to NLMPs in [14]. It can be shown that the bisimulation equivalence is a congruence for parallel composition of IOSA.…”
Section: Parallel Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another direction is to deal with systems that are more complex than LMPs. For example, we can add non-determinism choices for the same action, as the model in [11]. In addition, we can add the internal action τ to the set of actions and investigate weak bisimulations for LMPs, and investigate the metric definition for continuous-time models [20].…”
Section: Compositionalitymentioning
confidence: 99%
“…the identification of Hennessy-Milner classes. The few papers that do consider the problem of identifying HM classes seem to be concerned with probabilistic systems: see [5,6,7,17,8,3,1] for example. However, in most of these papers, the following quote is emblematic of the source of these results: "... the probabilistic systems we are considering, without explicit nondeterminism, resemble deterministic systems quite closely, rather than nondeterministic systems" [5].…”
Section: Introductionmentioning
confidence: 99%